Prevalence of Borrelia burgdorferi and Borrelia miyamotoi in questing Ixodes ricinus ticks from four sites in the UK - Layzell, S; Bailey, D; Peacey, M; Nuttall, P (Elsevier, 2017)
Borrelia miyamotoi is a spirochete bacterium related to Borrelia burgdorferi sensu lato, the cause of Lyme borreliosis, and vectored by ticks. In 2014, B. miyamotoi was identified in three questing Ixodes ricinus collected in the UK. We sought to confirm the presence of B. miyamotoi in the UK. Ticks were collected from four locations not previously investigated for B. miyamotoi or B. burgdorferi 20 s.l. and of which two are considered as Lyme borreliosis “hotspots” based on hospital records of the disease. We independently confirm that B. miyamotoi is present in the UK and support the view that B. miyamotoi is likely to have a broad geographic distribution, at low levels. Our study also adds to the existing data on the distribution of B. burgdorferi s.l. in the UK and demonstrates that although the two “hotspots” had relatively high tick densities, they did not have the highest proportion of infected ticks.